Attribution of intentions in autism spectrum disorder: A study of event‐related potentials - Fernandes, J. M.; Soares, S.; Lopes, R.; Jerónimo, R.; Barahona‐Corrêa, J. B. (Autism Research, 2022)
Autism spectrum disorder (ASD) is characterized by social cognition deficits, including difficulties inferring the intentions of others. Although deficits in attribution of intentions (AI) have been consistently replicated in ASD, their exact nature remains unexplored. Here we registered the electrophysiological correlates of a nonverbal social cognition task to investigate AI in autistic adults. Twenty-one male autistic adults and 30 male neurotypical volunteers performed a comic strips task depicting either intentional action (AI) or physical causality with or without human characters, while their electroencephalographic signal was recorded. Compared to neurotypical volunteers, autistic participants were significantly less accurate in correctly identifying congruence in the AI condition, but not in the physical causality conditions. In the AI condition a bilateral posterior positive event-related potential (ERP) occurred 200–400 ms post-stimulus (the ERP intention effect) in both groups. This waveform comprised a P200 and a P300 component, with the P200 component being larger for the AI condition in neurotypical volunteers but not in autistic individuals, who also showed a longer latency for this waveform. Group differences in amplitude of the ERP intention effect only became evident when we compared autistic participants to a subgroup of similarly performing neurotypical participants, suggesting that the atypical ERP waveform in ASD is an effect of group, rather than a marker of low-task performance. Together, these results suggest that the lower accuracy of the ASD group in the AI task may result from impaired early attentional processing and contextual integration of socially relevant cues. Lay Summary: To understand why autistic people have difficulties in inferring others' intentions, we asked participants to judge the congruence of the endings of comic strips depicting either intentional actions (e.g., fetching a chair to reach for something) or situations solely following physical rules (e.g., an apple falling on someone's head), while their electrical brain activity was recorded. Autistic individuals had more difficulties in inferring intentions than neurotypical controls, which may reflect impaired attention and contextual integration of social cues.